2014
DOI: 10.4269/ajtmh.13-0713
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Important Correlates of Maternal Education and Childhood Malaria Infections

Abstract: Abstract. The relationship between maternal education and child health has intrigued researchers for decades. This study explored the interaction between maternal education and childhood malaria infection. Cross-sectional survey data from three African countries were used. Descriptive analysis and multivariate logistic regression models were completed in line with identified correlates. Marginal effects and Oaxaca decomposition analysis on maternal education and childhood malaria infection were also estimated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
43
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 63 publications
16
43
2
1
Order By: Relevance
“…Specific infections that have been linked to maternal education include: diarrhea and pneumonia [32], chronic suppurative otitis media [33], Helicobacter pylori [33,35], and malaria [7]. A cross-sectional study of over 10,000 households in Tanzania, Uganda, and Angola investigating the relationship between maternal education and childhood malaria infection demonstrated that there is a negative relationship between maternal education and the risk of childhood malaria infection [7]. Our study confirms and extends these findings to another subSaharan African context, characterized by social disruption due to violent conflict.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Specific infections that have been linked to maternal education include: diarrhea and pneumonia [32], chronic suppurative otitis media [33], Helicobacter pylori [33,35], and malaria [7]. A cross-sectional study of over 10,000 households in Tanzania, Uganda, and Angola investigating the relationship between maternal education and childhood malaria infection demonstrated that there is a negative relationship between maternal education and the risk of childhood malaria infection [7]. Our study confirms and extends these findings to another subSaharan African context, characterized by social disruption due to violent conflict.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to maternal education, we identified multiple other independent predictors of childhood malaria (Table 3). In order to integrate these co-variates into a cohesive structure, we adapted a conceptual framework first proposed by Njau et al [7], linking maternal education to childhood malaria though several putative causal pathways (Supplemental Figure 1). Mothers with higher education: (1) may be more likely to access malaria prevention measures (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations